Removal of anionic dyes by adsorbents derived from Coix lacryma-jobi (Adlai) shells isotherm studies - Silvano, Marian Rose Luena; De Luna, Mark Daniel G. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
The presence of dyes in water bodies is a threat to aquatic biodiversity and a potential health risk to humans. In this study, acid-treated carbonized Adlai (ACA) and base-treated carbonized Adlai (BCA) prepared from Coix lacryma-jobi L. (Adlai) shells were used to remove Eriochrome Black T (EBT), Reactive Blue 19 (RB 19) and Reactive Red 120 (RR 120) from aqueous solution. The mechanism of dye adsorption by ACA and BCA was evaluated using Langmuir, Freundlich and Temkin isotherm models, and the pseudo-first order, pseudo-second order and intraparticle diffusion kinetic models. The Langmui1r model best describes the adsorption of each dye to ACA (R2 is 0.988 for EBT, 0.966 for RB 19 and 0.962 for RR 120) and BCA (R2 is 0.990 for EBT, 0.982 for RB 19 and 0.985 for RR 120), while the pseudo-second order model best fit adsorption of EBT on ACA and BCA (R2 is 0.988 and 0.991 respectively), RB 19 on ACA and BCA (R2 is 0.995 and 0.873 respectively), and RR 120 on BCA (R* is 0.990). Intraparticle diffusion was also observed for each dye onto ACA (R2 is 0.874, 0.857 and 0.965 for EBT, RB 19 and RR 120 respectively) and BCA (R2 is 0.816, 0.916 and 0.965 for EBT, RB 19 and RR 120 respectively).The uptake increased for EBT (0.821 mg/g to 1.004 mg/g and 0.229 mg/g to 0.301 mg/g for pH 6 to 7 on ACA and BCA respectively)and RR 120 (0.459 mg/g to 0.720 mg/g and 0.368 mg/g to 0.609 mg/g for pH 6 to 8 on ACA and BCA respectively),while uptake of RB 19 decreased (0.489 mg/g to 0.358 mg/g and 0.402 mg/g to 0.381 mg/g for pH 6 to 8 on ACA and BCA respectively).
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman
Keywords: Sewage -- Purification -- Color removal; Adsorption; Adlai shells